Employers 'don't care about computer injuries'. - Abbott D (Talkback Magazine, 2004)
Ergonomist Duncan Abbott, who specialises in redesigning workspaces and job tasks to improve comfort and safety, and to increase productivity, has written a detailed response, citing Health Safety legislation. This article appears in full on or our website: www.backcare.org. A brief excerpt from it appears below.In the October issue of talkback, which will focus on posture, the second part of Duncan's article will outline the problems for keyboard workers, and how to prevent them.